El emprendimiento como alternativa laboral para los graduados de la carrera de Ingeniería Comercial de la Universidad Técnica de Cotopaxi, cohortes 2018. - Pastas Taco, Angela Maricela (2020)
The work presented is mainly focused on investigating and analyzing the labor field of graduates of the Commercial Engineering career of the Technical University of Cotopaxi, and whose objective is to contribute with strategies to the formation of graduate ventures, which allow consolidation in the market. At the present time there is a deep economic crisis in the country that inevitably attacks recent graduates, the over-demand for professionals is also a mitigating factor because the sources of work are very few or scarce, therefore challenges are projected for the universities, considered as a fundamental and purposeful pillar, capable of contributing in the direction of social and economic development. If there is not enough support for graduate business initiatives, an obstacle will be generated when undertaking, which could have been very successful in the market, and on the contrary it remains stagnant, how important it is then that the academy not only stimulates professionals to develop business projects, but also provide special advice to achieve their consolidation and positioning. The theoretical framework used allowed to establish a scheme for the consolidation of the proposal; A clear research methodology was established by applying the instrument (survey) to a sample of 65 graduates, which was tabulated and interpreted the results obtained, verifying the relationship of the variables raised; and finally, through the conclusions and recommendations, the problem posed has been verified, this being the reason for raising the proposal of a Strategic Plan for graduates.